Methods of new technological developments of electric motors based on soft magnetic materials - Berdiev U. T.; Kolesnikov I. K.; Tuychieva M. N.; Khasanov F. F.; Sulaymonov U. B. (E3S Web of Conferences, 2023)
Application conditions of composite materials based on ASC100.29 iron powders with an oxide coating in electrical machine devices as a stator with improved performance are considered in the article. The conditions for increasing the stability of the operation of electric motors are determined based on changes in the thickness of the oxide layer. Three-dimensional models of magnetic circuits were used, which made it possible to achieve a force of up to 4500 N with a torque of 3 to 8 Nm, which made it possible to obtain an engine power of 100-200 W. As a result, experimental characteristics of dependences μ=f(h), H=f(h)) and the power of specific losses on the thickness of the oxide coating ωyд=f(h) were obtained. Methods for measuring the dynamic characteristics of the stator magnetic circuit are determined.